The Image of the Homeland in the Letters of Antanas Vaičiulaitis - Bankauskaitė, Gabija; Vaišvylaitė, Domantė (Respectus Philologicus, 2019)
The reflection of the homeland, the Lithuanian nation, the native land is very important in Antanas Vaičiulaitis’ creative work and personal correspondence. Letters, written 1924–1992 reveal a creative being, closely related to the formation of the image of Lithuania, its embodiment and the preservation of the memory of the motherland. The image of the homeland is often conveyed by the symbolism of a lost paradise, accompanied by the feelings of a tragic denouement. The construct of homeland as a paradise began to emerge in the writer’s early childhood, in letters it is portrayed as a mythical Eden. Through the mother, the space of home and the nature surrounding it, the metaphor of the motherland-fortress was formed. By comparing the homeland with his beloved mother, Antanas Vaičiulaitis conveyed the great pain, caused by the Lithuanian occupation. The letters’ image of homeland-paradise is associated with the ideals of patriotism, holiness of childhood and family, faith and also motives of loss and return, conveyed by the symbols of the tree and the bird. In the writer’s correspondence, through the personal context, complex emotional states reveal the cultural memory of the nation.
Keywords: Antanas Vaičiulaitis; letter; homeland; image; symbol